Nonlinear subsidence at Fremantle, a long-recording tide gauge in the Southern Hemisphere - Featherstone, Will; Penna, N.; Filmer, Michael; Williams, S. (2015)
© 2015 The Authors. A combination of independent evidence (continuous GPS, repeat geodetic leveling, groundwater abstraction, satellite altimetry, and tide gauge (TG) records) shows that the long-recording Fremantle TG has been subsiding in a nonlinear way since the mid-1970s due to time-variable groundwater abstraction. The vertical land motion (VLM) rates vary from approximately -2 to -4 mm/yr (i.e., subsidence), thus producing a small apparent acceleration in mean sea level computed from the Fremantle TG records. We exemplify that GPS-derived VLM must be geodetically connected to the TG to eliminate the commonly used assumption that there is no differential VLM when the GPS is not colocated with the TG. In the Perth Basin, we show that groundwater abstraction can be used as a diagnostic tool for identifying nonlinear VLM that is not evident in GPS time series alone. Key Points: The Fremantle tide gauge is and has been subsiding in a nonlinear way Exemplar of the need for geodetic connection between tide gauge and GPS station Groundwater has been used as a diagnostic for nonlinear vertical land movement.